UniLectin, A One‐Stop‐Shop to Explore and Study Carbohydrate‐Binding Proteins. Issue 11 (26th November 2021) - Imberty, Anne; Bonnardel, François; Lisacek, Frédérique
Abstract: All eukaryotic cells are covered with a dense layer of glycoconjugates, and the cell walls of bacteria are made of various polysaccharides, putting glycans in key locations for mediating protein‐protein interactions at cell interfaces. Glycan function is therefore mainly defined as binding to other molecules, and lectins are proteins that specifically recognize and interact non‐covalently with glycans. UniLectin was designed based on insight into the knowledge of lectins, their classification, and their biological role. This modular platform provides a curated and periodically updated classification of lectins along with a set of comparative and visualization tools, as well as structured results of screening comprehensive sequence datasets. UniLectin can be used to explore lectins, find precise information on glycan‐protein interactions, and mine the results of predictive tools based on HMM profiles. This usage is illustrated here with two protocols. The first one highlights the fine‐tuned role of the O blood group antigen in distinctive pathogen recognition, while the second compares the various bacterial lectin arsenals that clearly depend on living conditions of species even in the same genus. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. [Correction added on May 17, 2022, after first online publication: CSAL funding statement has been added.] Basic Protocol 1 : Searching for the structural details of lectins binding the O blood group antigen Basic Protocol 2 : Comparing the lectomes of related organisms in different environments